New isotopic evidence for micro and mesothermal valleys camelids from Northwest Argentina - Killian Galván, Violeta Anahí; Belotti López de Medina, Carlos Raúl; Bugliani, María Fabiana; Spano, Romina Clara (Frontiers in Environmental Archaeology, 2024)
IntroductionDomestic and wild camelids were the most significant meat resource for pre-Hispanic agropastoral societies in the Argentine Northwest's micro valleys (between 2,500 and 3,400 masl) and mesothermal valleys (2,500 and 1,500 masl), with varying relative importance in comparison to cultivated and collected plants. Examining pastoral movement techniques, as well as the areas available for wild resource gathering, allows us to acquire a better understanding of the nature and scale of social structure among these human communities. Stable isotope analyses of carbon (13C/12C; δ13C) and nitrogen (15N/14N; δ15N) provide efficient tools for understanding these features.MethodsThe article shows the bone collagen measurements of a sample of camelid bones from archaeofaunas recovered from Soria 2 sites (n = 7) and structure 93 of Loma l'Ántigo (n = 5), all in Catamarca province. The first is a residential unit in the Yocavil valley (2,400 masl), and its chronology corresponds to the beginning of the region's Formative Period. The second is in the Cajón Valley (2,700 masl) and dates to the Regional Developments Period. Bone specimens were previously categorized to genus or species rank employing morphological and osteometric criteria.ResultsOur results suggest that C4 plants have been important in animal diets since the Formative period. At the same time, access to pastures or wildlife at high altitudinal levels persisted during the Regional Developments, with the possibility of a fodder intensification strategy also based on C3 plants.DiscussionSuch kind of data allows us to assess whether a livestock intensification plan based on corn provision coincided with social, political, and economic changes in the early second millennium AD.